Negative results: Investigations into the quantification of silicone-based condom lubricants in solution by DRIFTS-FTIR - Burnier, Celine; Monzò, M.; Sauzier, Georgina; Lewis, Simon (Elsevier, 2022)
Condom (specifically silicone) lubricants are a form of trace evidence being increasingly submitted for examination in forensic investigations of sexual assault. Interpreting these traces requires an understanding of their transfer and persistence, such as being able to quantify the amount of transferred material as well as the loss percentage over time. However, to the best of our knowledge, an accurate quantification method for silicone polymers within a forensic context has not been reported. This study evaluated diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS), a commonly used method for qualitative analysis of condom evidence in casework, as an approach for the quantification or semi-quantification of silicone lubricants in solution. Although a general trend was observed between the DRIFTS signal and the silicone lubricant concentration, high variability between sample runs meant that these changes were not reproducible enough for quantitative prediction.